RESPON SISWA TERHADAP PEMBELAJARAN BERBASIS MASALAH PADA MATERI PENCEMARAN LINGKUNGAN DI KELAS X SMA - Kusuma, Apriadi Marki; Candramila, Wolly; Ariyati, eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study aimed to describe the process of problem-based learning and students’ responses on environmental pollution material in class X of SMA Taman Mulia Kubu Raya School Year (SY) 2016/2017. The form of study was a pre-experimental design with a one-shot case study. Research samples were 48 students of class XB and XC SMA Taman Mulia SY 2016/2017. Data were collected using observation sheet for classroom learning process and ARCS model of students’ responses questionnaire that included the response (relevance) and reaction (attention, satisfaction, and confidence) criteria. The observation data were analysed using Guttman scale while student responses using Likert scale. The research results showed that the teaching and learning process was conducted 100% in accordance with the five-stage problem-based learning model and the average students’ responses was categorized very positive with the score of 87.8%. This study also indicated that the problem-based learning model was very suitable for the teaching of environmental pollution material and giving positive students responses.Keywords: Problem-Based Learning, Student Responses, Environmental Pollution